Biological and structural properties of curcumin-loaded graphene oxide incorporated collagen as composite scaffold for bone regeneration - Qi Xie; Tianqi Wang; Lina He; Hongbo Liang; Jingxuan Sun; Xiaoxiao Huang; Weili Xie; Yumei Niu (Frontiers in Bioengineering and Biotechnology)
IntroductionTo address the challenges related to bone defects, including osteoinductivity deficiency and post-implantation infection risk, this study developed the collagen composite scaffolds (CUR-GO-COL) with multifunctionality by integrating the curcumin-loaded graphene oxide with collagen through a freeze-drying-cross-linking process.MethodsThe morphological and structural characteristics of the composite scaffolds were analyzed, along with their physicochemical properties, including water absorption capacity, water retention rate, porosity, in vitro degradation, and curcumin release. To evaluate the biocompatibility, cell viability, proliferation, and adhesion capabilities of the composite scaffolds, as well as their osteogenic and antimicrobial properties, in vitro cell and bacterial assays were conducted. These assays were designed to assess the impact of the composite scaffolds on cell behavior and bacterial growth, thereby providing insights into their potential for promoting osteogenesis and inhibiting infection.ResultsThe CUR-GO-COL composite scaffold with a CUR-GO concentration of 0.05% (w/v) exhibits optimal biological compatibility and stable and slow curcumin release rate. Furthermore, in vitro cell and bacterial tests demonstrated that the prepared CUR-GO-COL composite scaffolds enhance cell viability, proliferation and adhesion, and offer superior osteogenic and antimicrobial properties compared with the CUR-GO composite scaffold, confirming the osteogenesis promotion and antimicrobial effects.DiscussionThe introduction of CUR-GO into collagen scaffold creates a bone-friendly microenvironment, and offers a theoretical foundation for the design, investigation and utilization of multifunctional bone tissue biomaterials.